Dance of the planets : the universe of Nicolaus Copernicus - Veglahn, Nancy; Ulrich, George (New York : Coward, McCann & Geohegan, 1979)
Nicolaus Copernicus' inquiring mind probes the secrets of the universe during a time when such behavior is considered heretical.
Bibliography: p. 63.
Keywords: Copernicus, Nicolaus, -- 1473-1543 -- Juvenile literature; Copernicus, Nicolaus, -- 1473-1543.; Astronomers -- Poland -- Biography -- Juvenile literature; Astronomers